Fundamentals of Finance: Finance Management, Investment, Capital Market, and Funding - Indra Wahyu Putra, Christophorus; Panatap Soehaditama, Josua; Yusuf Kurniawan, Mohamad; Mulyani Setyowati, Tri; Sova, Maya (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2024)
The purpose of this literature research is expected to build a hypothesis regarding the influence between variables that can later be used for further research in the scope of financial management. The research article Literature Review Fundamental of Finance: Finance Management, investment, Capital Market, and Funding is a scientific literature article in the scope of financial management science. The approach used in this literature review research is descriptive qualitative. The data collection technique is to use literature studies or conduct a review of previous relevant articles. The data used in this descriptive qualitative approach comes from previous research that is relevant to this research and is sourced from academic online media such as Thomson Reuters Journal, Springer, Taylor & Francis, Scopus Emerald, Sage, WoS, National Accredited Journal (SINTA), DOAJ, EBSCO, Google Scholar and digital reference books. The results of this literature review article are: 1) Finance Management plays a role in the Fundamentals of Finance; 2) Investment plays a role in the Fundamentals of Finance; 3) Capital Market plays a role in the Fundamentals of Finance; and 4) Funding plays a role in the Fundamentals of Finance.